Portais corporativos como ferramenta para o relacionamento com o cliente - Ficher, Neide Caldeirão (2009)
While still evolving in the real environment, the discussion about client relationship is advancing towards the virtual world, what makes relationship marketing, the internet and the cooperative portals part of the new daily routine of the companies. Since they are considered to be a probable solution to the client relationship in the virtual world, the cooperative portals are the main topic in this dissertation whose intent is to investigate in what way the cooperative portals contribute towards promoting and improving the relationship between the companies and their clients. In order to fulfill the objectives of this dissertation, this research was defined as being exploratory based on a single case-study. For the analysis of the problem, the first phase aimed at comprehending the strategic objectives of the company regarding its cooperative portal and the tools used to create and improve the client relationship through the cooperative portal. The investigation was carried out using in-depth interviews with the executives who are directly involved in the cooperative portal of the company being studied. Using the sequenced triangulation, the result obtained from the interviews provided a basis for the second phase of the investigation, the survey carried out with the clients of the company being studied. This second part investigated the relationship of the client with the cooperative portal, their understanding and perception regarding the same points that the company had indicated to be its objectives for the portal. At the end of the study, the objectives of the company and the perceptions of the clients were compared, what led to considerations about the portal s efficiency in attaining the objectives of the relationship marketing and also its contributions to a better placement of the tools available in the portal in face of the company s strategy and also the clients needs and expectations